2017
DOI: 10.17582/journal.jahp/2017/5.3.115.119
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Contamination of Raw Meat and Butchers Equipment in Retail Shops in Tando-Allahyar, Pakistan

Abstract: | The present study was performed to evaluate the aerobic bacterial contamination in meat and butchers' equipment in retail shops in Tando-Allahyar, Pakistan. A total of 100 samples (40 beef, 40 mutton and 20 butchers' meat-cutting equipment) were obtained from butcher shops from local vendors of different regions of Tando-Allahyar. The samples were collected randomly in sterile labelled polythene bags or bijoux bottles individually and were transferred to laboratory at 4 o C within 3-4 hours of collection. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…All raw meat samples exhibited the higher (p < 0.05) bacterial load as compared to their corresponding cooked meat. Similar results were recorded by Bughti et al (2017) who reported higher bacterial count (4.1×10 9 CFU/g) in raw beef than mutton (3.9×10 7 CFU/g) and butcher's equipment sample (3.7×10 6 ) respectively. Ayaz et al (1985) reported bacterial count as 3.0×10 8 CFU/g in beef, chicken and lamb shawarma from different restaurants.…”
Section: Bacterial Load In Raw and Cooked Beef Mutton And Fishsupporting
confidence: 88%
“…All raw meat samples exhibited the higher (p < 0.05) bacterial load as compared to their corresponding cooked meat. Similar results were recorded by Bughti et al (2017) who reported higher bacterial count (4.1×10 9 CFU/g) in raw beef than mutton (3.9×10 7 CFU/g) and butcher's equipment sample (3.7×10 6 ) respectively. Ayaz et al (1985) reported bacterial count as 3.0×10 8 CFU/g in beef, chicken and lamb shawarma from different restaurants.…”
Section: Bacterial Load In Raw and Cooked Beef Mutton And Fishsupporting
confidence: 88%
“…As indicated in Table 5, butcher shop customers had different meat preparation preferences including raw meat preparation. The meat preparations (cooking and roasting) are methods of foodborne disease prevention [1,14]. As a result, the meat preparation practices of the butcher shop workers are depending on their knowledge about the potentiality of preparation methods in reducing foodborne diseases [17,36].…”
Section: Discussionmentioning
confidence: 99%
“…Meat is rich in essential protein and valuable nutrients for human health. Despite these benefits, it is a favorable medium of microbial growth and transmission to humans [ 1 ]. Especially, meat contaminations from meat handlers’ bodies, the hide of animals, the gastrointestinal system of the animals, and the meat processing environment are the common health risks for the meat consumers [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meat at all kinds (large animals, poultry and aquatic animals) is one of the most valuable and beneficial food sources, where, it consists of protein, amino acids, mineral salts, fats, fatty acids, vitamins in addition to carbohydrates (Mansour et al, 2019). Raw meat contributes by 90% to the transmission of pathogens ، which responsible of food-borne illness in humans especially bacterial agents due to its chemical characteristics leading to expansion of a wide range of microbial communities (Bughti et al, 2017;Nagarajan et al, 2018;Rasheed, 2012). Typically, meat of healthy animals is sterile; so microbiological quality of any meat kinds depends on the health and physical status of the animal.…”
Section: Introductionmentioning
confidence: 99%